2022
DOI: 10.23960/jhptt.12268-76
|View full text |Cite
|
Sign up to set email alerts
|

The effect of biopesticide and combined fertilization in promoting plant health and growth of tomato cultivated on peat soil in West Kalimantan

Abstract: The demand for horticultural products that are cultivated organically has increased. However, the susceptibility of plants to pests and diseases becomes an obstacle in organic crop cultivation. The use of biopesticides can be a solution to overcome these problems with the added benefit due to its environmental friendly and sustainable aspect. The purpose of this study was to determine the effect of biopesticides and combined fertilization in promoting plant health and enhancing tomato growth on the peat soil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Relevant to that study, another study of Rinaldi and Nugrahapsari, 2017 [ 44 ], showed that vegetable growing in Bali retained comparative and competitive advantages, particularly in farming commodities such as red chili, cayenne pepper, and tomato, with PCR and DRCR coefficient values of less than 1. Moreover, the results of a study conducted by Widiastuti and Umar, 2021 [ 45 ] on the impact of combining biopesticides and fertilizers provided interesting results showing that the treatment gave the highest tomato productivity. It indicated that industrial biopesticides could be a good alternative to replace chemical pesticides, while dependence on inorganic fertilizers was difficult to avoid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Relevant to that study, another study of Rinaldi and Nugrahapsari, 2017 [ 44 ], showed that vegetable growing in Bali retained comparative and competitive advantages, particularly in farming commodities such as red chili, cayenne pepper, and tomato, with PCR and DRCR coefficient values of less than 1. Moreover, the results of a study conducted by Widiastuti and Umar, 2021 [ 45 ] on the impact of combining biopesticides and fertilizers provided interesting results showing that the treatment gave the highest tomato productivity. It indicated that industrial biopesticides could be a good alternative to replace chemical pesticides, while dependence on inorganic fertilizers was difficult to avoid.…”
Section: Literature Reviewmentioning
confidence: 99%